The Production of Supplementary Learning Materials of Arabic Grammatology Based on The Curriculum 2013 with Scientific Approach at The First State Islamic Senior Hight School Malang - Shobirin, Abdurrahman; Wargadinata, Wildana; Hasan, Nur (Institut Agama Islam Negeri (IAIN) Kediri, 2020)
Arabic language book used by a student of of the first state islamic senior hight school Malang city head for commanding every language skills, there are listenig, reading, speaking, and writing. However the content within a book is not complete yet with arabic grammatology materials that it was agreeable by scientific approach in curriculum 2013. So, the book need supplementary learning materials to complete teaching complement. This research is development research use Borg and Gall model that it consist of 10 steps. This reserach use observation, interview, questioner, and test even gotten the data such quallitative and quatitative data. Research findings: (1) researcher was produced supplementary learning materials called by “al-mutammim” because it was be complement based on student needs. (2) based on produc validation values by the book design validator and the content of the nahwu material, this teaching material worthy of use at The Islamic State Senior High School. (3) this teaching materials able to upgrade student’s understanding and using this teaching materials was be effective for him